Peran Aren Handicraft dalam Pelestarian Kerajinan Lokal dan Inovasi Pemasaran Digital di Jember - Ferdiyansah, Muchammad Nur Haqikad; Adelia, Adelia; Hendrianto, Diki; Lestari, Yunita Puji; Nurkhofiah, Siti; Bachtiar, Da’i; Amalia, Syemalia Azka; Rizqiah, Shilna Maftuhatar (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study aims to examine the role of Aren Handicraft in preserving local crafts and exploring digital marketing strategies applied to improve product competitiveness in the modern era. Using a qualitative descriptive approach, data were obtained through observation, in-depth interviews, and documentation of digital marketing activities. The results of the study indicate that Aren Handicraft has succeeded in maintaining traditional production techniques by utilizing natural materials from the aren tree, which not only strengthens local cultural identity but also adds authentic value to the product. In facing the challenges of globalization, this business adopts a digital marketing strategy through social media and e-commerce platforms, which have proven effective in expanding market reach and increasing sales. In addition to the economic aspect, Aren Handicraft also contributes to community empowerment, especially women and marginalized groups, through job creation and skill improvement. The successful integration between the preservation of tradition and technological innovation makes Aren Handicraft an example of good practice in developing MSMEs based on local wisdom. If there is a business, support for technology training and digital infrastructure from various parties is needed. The results of this study provide strategic insights in developing a highly competitive local creative industry in the digital era.